U-Pb detrital zircon geochronology of the Dalradian Supergroup, Shetland Islands, Scotland: Implications for regional correlations and Neoproterozoic-Palaeozoic basin development - Strachan, R.; Prave, A.; Kirkland, Chris; Storey, C. (2013)
U-Pb detrital zircon data show that the East Mainland Succession, the presumed correlative of the Dalradian Supergroup in the Shetland Islands, Scotland, is dominated by Mesoproterozoic and Archaean material, with some Palaeoproterozoic detritus. The data are most consistent with derivation from eastern Laurentia, although western Baltica sources cannot be excluded. A magmatic event at c. 576 Ma supplied detritus to the Clift Hills Group, and was the source of high-temperature fluids that resulted in growth of new metamorphic zircon, and altered old detrital grains within the underlying sedimentary pile. This provides a constraint on the age of the global Shuram-Wonaka event recognized within the Whiteness Group, which underlies the Clift Hills Group. The presence of common Archaean detritus is compatible with broad timecorrelation of the East Mainland Succession with the Dalradian Supergroup. However, differences in age, thickness and basin evolution are consistent with deposition in separate basins along the extending Laurentian margin during supercontinent break-up and development of the Iapetus Ocean. Similarities in the detrital zircon records of the East Mainland Succession and the offshore Devonian-Carboniferous Clair Group permit derivation, at least in part, of the latter from the Shetland Islands and proximal sources on the adjacent continental shelf.